## x + 3 = 3 (11 – 3x)

### x = 3

To solve for x in the given equation, we need to isolate x on one side of the equal sign.

Step 1: Distribute the 3 outside the parentheses on the right-hand side of the equation:

x + 3 = 33 – 9x

Step 2: Add 9x to both sides to eliminate the x term on the right side:

10x + 3 = 33

Step 3: Subtract 3 from both sides to isolate the variable term:

10x = 30

Step 4: Solve for x by dividing both sides by 10:

x = 3

Therefore, the solution to the given equation is x = 3.

Checking the answer:

Substituting x = 3 back into the original equation:

3 + 3 = 3(11 – 3(3))

6 = 6

The left side of the equation is equal to the right side, so the solution x = 3 is correct.

##### More Answers:

Solve 2(3X + 1) = 7X – 5 With Step-By-Step GuidanceLearn How To Solve Equations: Step-By-Step Guide To Find The Solution To 3X = 2(7) + 2(5X)

Step-By-Step Guide To Solving The Equation 2X – 4 = -4(X – 5)

Error 403 The request cannot be completed because you have exceeded your quota. : quotaExceeded